Technologies for the Production of Meat Products with a Low Sodium Chloride Content and Improved Quality Characteristics—A Review - Kim, Tae-Kyung (Foods, 2021)
In recent years, consumer concerns regarding high levels of sodium chloride (NaCl) intake have increased, given the associated risk of cardiovascular disease. This has led food industries to consider lowering the use of sodium in food products. However, it is well known that the addition of NaCl to meat products enhances their quality, including water-holding capacity, emulsification capacity, juiciness, and texture. Thus, it is difficult to completely remove salt from meat products; however, it is possible to reduce the salt content using salt substitutes, flavor enhancers, textural enhancers, or other processing technologies. Several recent studies have also suggested that processing technologies, including hot-boning, high pressure, radiation, and pulsed electric fields, can be used to manufacture meat products with reduced salt content. In conclusion, as the complete removal of NaCl from food products is not possible, combined technologies can be used to reduce the NaCl content of meat products, and the appropriate technology should be chosen and studied according to its effects on the quality of the specific meat product.